The Issues of Secession in the Process of the Rise and Fall of States in the Light of International Law - Diallo, Boubacar Sidi (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The aims of this contribution is to check the validity of the old theory, which goes back to Jellinek but is still dominant, which states that secession as well as the process of forming a new state, fall under the scope of a “simple fact” and thereby escape through definition to any law of way. According to this theory, secession is not a question of “Law” but a question of pure fact, failure or success: if a secessionist movement succeeds in establishing a new effectiveness, that is to say, puts in place the “Constituent elements” of a state, a new state is born. It is interesting to observe that with the phenomenon of the rise or the collapse of States, from the global perspective of international order and especially from the point of view of international law, the States concerned are, in practice, not simply left to their fate. On the contrary, the rise or the collapse of a State anywhere in the world is seen as a matter of concern for the international community, since the international system as a whole is felt to be affected. In such cases, international reactions have not been manifested primarily through the States as such, either indi-vidually or together. Basically, these reactions had to cope with the dilemma of choos-ing between two fundamental principles of legitimacy in international law: on the one hand, the sovereignty and equality of States and, on the other, the right of peoples to self-determination.